Economics and Public Health: Two Perspectives on Firearm Injury Prevention. Issue 1 (November 2022) - Glasser, Nathaniel J.; Pollack, Harold A.; Ranney, Megan L.; Betz, Marian E.
Firearm injury is a major cause of death, disability, and other harms to community well-being across the U.S. Economics and public health offer two complementary perspectives to conceptualize gun violence and formulate strategies to mitigate related harms. Economics offers methods and procedures for tabulating costs of firearm injury and offers an explicit, albeit imperfect normative framework to evaluate proposed interventions. Economics' focus on incentives, trade-offs, and resources constraints provides useful mechanisms for understanding illegal firearm markets and firearm use that can inform crime reduction efforts. Public health methods and interventions help to measure patterns of illness and disease, identify risks and protective factors, and inform prevention efforts for the most vulnerable individuals and communities. Public health also focuses attention on social determinants and structural factors in designing and evaluating interventions to prevent, address, and mitigate the consequences of gun violence.